Experiencing Verdi : a listener's companion - Sanders, Donald C., 1949- (Lanham, Md. : Scarecrow Press, 2014)
Along with his contemporaries Chopin and Wagner, Verdi is among the few composers whose place in the musical pantheon is based almost entirely upon the mastery of a single genre. This is largely owing to his staggering output in a career that lasted over fifty years. Several of his operas comprise the nucleus of the modern repertoire, and he almost single-handedly maintained the Italian lyric tradition against the tide of Wagnerian music drama. In his final years, he virtually reinvented Italian opera. Indeed, Verdi's life and music came to be so intimately associated with the Italian unification movement known as the Risorgimento that he is still revered as a great national figure in his homeland. Donald Sanders combines biography with simple, concise musical analysis. Summarizing the evolution of Italian opera and the bel canto tradition that prevailed at the beginning of Verdi's career, Sanders takes readers on a leisurely tour of eleven of Verdi's most important operas and of the 'Manzoni Requiem' and concludes with a look at Verdi's influence.
Italian opera before Verdi -- The early years : Oberto -- Change of fortune and years in the galleys : Nabucco, Macbeth -- Signora Verdi, new hopes for Italy, and three iconic operas : Rigoletto, Il Trovatore, La Traviata -- Verdi the statesman : Un ballo in maschera, Don Carlos -- Return to Milan : Aida, Manzoni requiem -- The final masterworks : Otello, Falstaff -- Death of the maestro.
Includes bibliographical references and index.
Keywords: Verdi, Giuseppe, -- 1813-1901 -- Criticism and interpretation; Verdi, Giuseppe, -- 1813-1901.; Opera -- Italy -- 19th century